Characterizing distributions, composition profiles, sources and potential health risk of polybrominated diphenyl ethers (PBDEs) in the coastal sediments from East China Sea. (June 2016) - Wang, Guoguang; Peng, Jialin; Zhang, Dahai; Li, Xianguo
Abstract: Sediment samples ( n = 20) were collected from Yangtze River Estuary (YRE) and the adjacent East China Sea (ECS) inner shelf to explore spatial and temporal distributions, environmental fate, sources and potential health risk of polybrominated diphenyl ethers (PBDEs). Concentrations of BDE-209 and total 7 PBDEs (without BDE-209; ∑7 PBDEs) ranged from 62.3 to 1758 pg g −1 and from 36.9 to 233.6 pg g −1 dry weight, respectively; both of the highest values occurred near the city of Wenzhou. Concentrations of BDE-209 and ∑7 PBDEs both indicated a decreasing trend from inshore areas toward outer shelf. Significantly positive linear correlations were only observed between logBDE-183 concentrations and TOC/grain size ( r 2 = 0.6734 and 0.5977 for TOC and grain size, respectively) as well as BDE-209 and TOC/grain size ( r 2 = 0.4137 and 0.5332 for TOC and grain size, respectively) in the north of 28 ° N, indicating that YR had significant influence on the distribution of higher brominated congeners only in the north part. Depth profiles of PBDEs in a sediment core P01 ( n = 1, m = 11) collected from YRE showed that the input of BDE-209 gradually increased from 1930 to 2010, while the levels of ∑7 PBDEs peaked in 1986 and obviously decreased in recent years. Partial Least-Squares Regression (PLSR) revealed that PBDEs in the coastal ECS were mainly from direct discharge of local anthropogenic activities (80.7%), followed by surface runoff of contaminated soils (15.1%), microbial degradation after sedimentation (2.6%) and photodegradation during atmospheric transportation (1.6%). The cancer risk of human exposure to BDE-209 at the 95% confidence level was 3.09 × 10 −7, 1.67 × 10 −7 and 8.86 × 10 −7 for children, teens and adults, respectively, significantly lower than the threshold level (10 −6 ). Hazard index (HI) calculated for non-cancer risk was also far less than 1 for the three groups, suggesting no non-cancer risk. Highlights: A 90-year high-resolution deposition record of PBDEs was studied. The YR influenced distribution of BDE-183 and -209 in ECS. Results suggested the debromination of BDE-209 in sediments. PBDEs originated from local sources, surface runoff, degradation in ECS. Cancer and non-cancer risks of the exposure to PBDEs were low for three age groups. Abstract : Capsule: The sources of PBDEs in East China Sea coastal sediments and the related human health risk were quantitatively analyzed.